If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6 + 4x) = 176 (6 * 8 + 4x * 8) = 176 (48 + 32x) = 176 Solving 48 + 32x = 176 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 32x = 176 + -48 Combine like terms: 48 + -48 = 0 0 + 32x = 176 + -48 32x = 176 + -48 Combine like terms: 176 + -48 = 128 32x = 128 Divide each side by '32'. x = 4 Simplifying x = 4
| Y=3*-7+11 | | 12/9-2 | | 5.7+1.9x=11.4 | | (-5)p+4(1-p)=(-2)p+(-3)(1-p) | | 140=4(x+10s)+30s | | 48x^2-12x-18=0 | | Z/1.22=-27 | | (3-z)(5z-1)=0 | | x(x+44)=0 | | 2.69=x-1 | | -2n(5n-7)=0 | | -(p+3)+2p-6=10 | | 4xsquared-6x-1=0 | | -6x-2(-2x-5)=-2 | | 2y^2-15y+22=0 | | (-5)p+(-2)(1-p)=4p+(-3)(1-p) | | X^2=16+[(x+4)*(x-4)] | | 6[(53)4]2= | | 4[-p+(-r)]= | | 3(7+5x)=96 | | ln(y)= | | (5*3)+9.5x+50=5+35x | | 7/2r-8=15/4r-10 | | (47-2x)(23-2x)=1081 | | 0x+3y=12 | | 7[-h+(-p)]= | | 9x+19=6(8-6x) | | 47x=109 | | 100p+(-90)(1-p)=(-80)p+70(1-p) | | 4(x-4)(4x+1)=0 | | 26z=78 | | 4(x+2)=-32 |